Role of donors in triggering second order non-linear optical properties of non-fullerene FCO-2FR1 based derivatives: A theoretical perspective. Issue 2 (February 2023) - Khalid, Muhammad; Khan, Mashal; Shafiq, Iqra; Mahmood, Khalid; Nadeem Akhtar, Muhammad; Iqbal, Javed; Al-Sadoon, Mohammad Khalid; Zaman, Wajid; Carmo Braga, Ataualpa Albert
Abstract: The organic compounds are known as an emerging class in the field of nonlinear optical (NLO) materials. In this paper, D–π–A configured oxygen containing organic chromophores (FD2-FD6 ) were designed by incorporating various donors in the chemical structure of FCO-2FR1 . This work is also inspired by the feasibility of FCO-2FR1 as an efficient solar cell. Theoretical approach involving DFT functional i.e ., B3LYP/6-311G(d, p) was utilized to achieve useful information regarding their electronic, structural, chemical and photonic properties. The structural modifications revealed significant electronic contribution in designing HOMOs and LUMOs for the derivatives with lowered energy gaps. The lowest HOMO-LUMO band gap obtained was 1.223 eV for FD2 compound in comparison to the reference molecule (FCO-2FR1 ) i.e., 2.053 eV. Moreover, the DFT findings revealed that the end-capped substituents play a key role in enhancing the NLO response of these push-pull chromophores. The UV–Vis spectra of tailored molecules revealed larger λ max values than the reference compound. Furthermore, strong intramolecular interactions showed the highest stabilization energy (28.40 kcal mol -1 ) for FD2 in the natural bond orbitals (NBOs) transitions, combined with the least binding energy (-0.432 eV). Successfully, the NLO results were favorable for the same chromophore (FD2 ) which showed the highest value for dipole moment ( μ tot  = 20.049 D ) and first hyper-polarizability ( β tot  = 11.22 × 10 -27   esu ). Similarly, the largest value for linear polarizability ⟨ α ⟩ was obtained as 2.936 × 10 -22   esu for FD3 compound. Overall, the designed compounds were calculated with greater NLO values as compared to FCO-2FR1 . The current study may provoke the researchers towards designing of highly efficient NLO materials via using the suitable organic linking species.